Social support and health-related quality of life among hepatitis C patients in Pahang, Malaysia - Zainulabid, Ummu Afeera; Md Jalil, Muhammad Ateeq; Jaafar, Khairul Azhar; Mohd Ibrahim, Mohamad Shafiq; M Yunus, Raudah (Wiley-Blackwell, 2021)
Background and Aim: Hepatitis C is one of the most common causes of liver disease worldwide. Health impacts of hepatitis C are not limited to physical morbidity but include psychosocial dimensions such as quality of life (QOL), depression, anxiety, and stigmatization. In Malaysia, modifiable factors that can improve QOL among hepatitis C patients have not been adequately studied. Our study aims to test the association between social support and QOL among hepatitis C patients. Methods: Employing a cross-sectional design, 195 hepatitis C patients who attended Hospital Tengku Ampuan Afzan—the main public tertiary hospital in Pahang—were recruited through convenience sampling. Social support was assessed using the Duke Social Support Index (DSSI) while health-related quality of life (HRQOL) was measured by 36-item shortform survey (SF-36v2). Results: We found a significant positive correlation between social support and physical (95% confidence interval [CI]: 0.132, 0.406; p < 0.05) and mental (95% CI: 0.224, 0.490; p < 0.05) dimension of HRQOL. Patients with good social support scores were more likely to have better HRQOL. Conclusion: There is association between social support and HRQOL among our respondents. Supportive family and friends can enhance the physical, emotional, and social function of a hepatitis C patient. Health-care providers should consider the role of social support to improve hepatitis C management, through a multidisciplinary approach.